2001
DOI: 10.1007/bf03179257
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth and fracture toughness properties of 304 stainless steel pipe for LNG transmission

Abstract: The fatigue crack growth rate and fracture toughness tests of type 304 stainless steel were studied over a temperature range of -162 o C to room temperature. Girth weld metal specimens were fabricated using a combination of gas-tungsten-arc-welding and shielded-metal-arc-welding. The seam weld metal was made with submerged arc welding. Fatigue crack growth rate tests were conducted using compact tension specimens in accordance with ASTM E647. Fracture toughness was evaluated through CTOD tests with three point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…The S-N fatigue tests were conducted on a servo-hydraulic testing machine (Instron Model 8516) at an R ratio of 0.1 under a uniaxial loading condition with a sinusoidal frequency of 30 Hz at 298 K and 110 K, respectively, in accordance with ASTM E466 [34]. The run-out fatigue specimens were defined as those not failed up to 2×10 6 cycles. An environmental chamber was utilized to maintain the testing temperature of 110 K which is the temperature of LNG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S-N fatigue tests were conducted on a servo-hydraulic testing machine (Instron Model 8516) at an R ratio of 0.1 under a uniaxial loading condition with a sinusoidal frequency of 30 Hz at 298 K and 110 K, respectively, in accordance with ASTM E466 [34]. The run-out fatigue specimens were defined as those not failed up to 2×10 6 cycles. An environmental chamber was utilized to maintain the testing temperature of 110 K which is the temperature of LNG.…”
Section: Methodsmentioning
confidence: 99%
“…The steels with Mn contents ranging from 15 to 30 wt% are under consideration for the application in a variety of fields, such as the material for LNG liquified natural gas (LNG) tankage [5][6][7][8] and cryogenic pipelines in offshore industry [4]. While the plastic deformation of high Mn steel is mostly accommodated by the slip mechanism, TRIP/TWIP effect can also contribute the deformation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…While effects of high temperatures on material behavior are well covered in international standards and guidelines, there is no comprehensive guidance for sub-zero temperature fatigue strength assessment of welded joints. This is likely related to the small number of publications concerning fatigue of welded steel joints at sub-zero temperatures, see [6][7][8][9][10][11][12][13][14][15][16][17]. Moreover, the majority of studies focuses on fatigue crack growth (FCG) rate testing for cryogenic applications and butt-welded joints.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue crack growth study in pressure vessels and piping is being carried out by many researchers [13][14][15][16][17][18][19][20][21][22][23] . Darcis et al 18 reported the experimental investigation of fatigue crack growth rates in ferrite-pearlite pipeline steels using curved middle-tension M(T) specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Darcis et al reported the experimental investigation of fatigue crack growth rates in ferrite–pearlite pipeline steels using curved middle‐tension M(T) specimens. In most of the cases, standard specimens or non‐standard specimens, directly fabricated from actual components, were used for experimentation and/or finite element analysis. It was altogether concluded that the fatigue and fracture properties predicted from these specimens were conservative because of the difference in constraint effect in real structural components.…”
Section: Introductionmentioning
confidence: 99%